Salt-Related MYB1 Coordinates Abscisic Acid Biosynthesis and Signaling during Salt Stress in Arabidopsis. Issue 2 (4th August 2015) - Wang, Ting; Tohge, Takayuki; Ivakov, Alexander; Mueller-Roeber, Bernd; Fernie, Alisdair R.; Mutwil, Marek; Schippers, Jos H.M.; Persson, Staffan
Abstract : A salt-related transcription factor regulates abscisic acid synthesis and signaling genes in germinating Arabidopsis seeds under saline conditions. Abstract: Abiotic stresses, such as salinity, cause global yield loss of all major crop plants. Factors and mechanisms that can aid in plant breeding for salt stress tolerance are therefore of great importance for food and feed production. Here, we identified a MYB-like transcription factor, Salt-Related MYB1 (SRM1), that negatively affects Arabidopsis ( Arabidopsis thaliana ) seed germination under saline conditions by regulating the levels of the stress hormone abscisic acid (ABA ). Accordingly, several ABA biosynthesis and signaling genes act directly downstream of SRM1, including SALT TOLERANT1 / NINE-CIS-EPOXYCAROTENOID DIOXYGENASE3, RESPONSIVE TO DESICCATION26, and Arabidopsis NAC DOMAIN CONTAINING PROTEIN19 . Furthermore, SRM1 impacts vegetative growth and leaf shape. We show that SRM1 is an important transcriptional regulator that directly targets ABA biosynthesis and signaling-related genes and therefore may be regarded as an important regulator of ABA -mediated salt stress tolerance.